Twilight, a Novel Circadian-Regulated Gene, Integrates Phototropism with Nutrient and Redox Homeostasis during Fungal Development - Deng, Yi Zhen (2015)
Phototropic regulation of circadian clock is important for environmental adaptation, organismal growth and differentiation. Light plays a critical role in fungal development and virulence. However, it is unclear what governs the intracellular metabolic response to such dark-light rhythms in fungi. Here, we describe a novel circadian-regulated Twilight (TWL) function essential for phototropic induction of asexual development and pathogenesis in the rice-blast fungus Magnaporthe oryzae. The TWL transcript oscillates during circadian cycles and peaks at subjective twilight. GFP-Twl remains acetylated and cytosolic in the dark, whereas light-induced phosphorylation (by the carbon sensor Snf1 kinase) drives it into the nucleus. The mRNA level of the transcription/repair factor TFB5, was significantly down regulated in the twl∆ mutant. Overexpression of TFB5 significantly suppressed the conidiation defects in the twl∆ mutant. Furthermore, Tfb5-GFP translocates to the nucleus during the phototropic response and under redox stress, while it failed to do so in the twl∆ mutant. Thus, we provide mechanistic insight into Twl-based regulation of nutrient and redox homeostasis in response to light during pathogen adaptation to the host milieu in the rice blast pathosystem.